Self Control terhadap Kekerasan dan Bullying Menurut Perspektif Al-Qur'an (Studi Al-Qur'an Tematik) - Puspita Fajriany Hudaya; Muhammad Alif (PT. Saha Kreasi Indonesia, 2026)
This research examines the concept of self-control against violence and bullying from the perspective of the Qur'an using a Structured Thematic Analysis (STA) approach that adopts Grounded Theory principles, including sensitizing concept, theoretical sampling, open coding, axial coding, selective coding, constant comparative analysis, record, and data saturation. Primary data were collected from 20 relevant Qur'anic verses, then analyzed through these stages as well as exegetical triangulation from various classical and contemporary Qur'anic commentaries. The findings reveal ten main aspects of self-control: emotional reaction control, anger suppression (kazhm al-ghaizh), revenge control, transformation of violence into goodness, internal self-change, non-violent responses to provocation, positive communication, avoidance of superior attitude, strategy of turning away from provocation, and manifestation of self-control in gentle and forgiving social relations. The research concludes that the Qur'an offers a comprehensive and hierarchical framework of self-control, ranging from internal control to social actualization, which is effective in preventing and addressing violence and bullying in various contexts, both in the real world and in digital spaces.